2022
DOI: 10.2147/idr.s386082
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Antibiotic Resistance in Egypt: A Single-Center Study

Abstract: Helicobacter pylori (H. pylori) is the most common human bacterial infection worldwide, infecting approximately half of the world's population. Although antibiotic use is indicated for H. pylori eradication, the recommended type of antibiotic varies from country to country according to the H. pylori resistance pattern; developing countries, such as Egypt, may have different patterns than developed countries. We evaluated the antibiotic resistance of H. pylori in Egypt. Methods: This cross-sectional study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
6
13
1
Order By: Relevance
“…In the current study, susceptibility testing showed that clarithromycin resistance was 54.5%, this agreed with Metwally et al (20) who found clarithromycin resistance (40%),…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the current study, susceptibility testing showed that clarithromycin resistance was 54.5%, this agreed with Metwally et al (20) who found clarithromycin resistance (40%),…”
Section: Discussionsupporting
confidence: 93%
“…Regarding amoxicillin resistance in our study, it was universal as all (100%) patients showed resistance. This was similar to Metwally et al (20) and Mabeku et al (26) studies as they reported very high resistance rate (97.1% and 97% respectively). On the opposite side, lower rates of resistance were detected in other studies by Shao et al (29) and Tang et al (21) who reported a rate of 1.6% and 7.7% respectively.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations